Cover Picture: A Stable Single‐Site Palladium Catalyst for Hydrogenations (Angew. Chem. Int. Ed. 38/2015). Issue 38 (7th August 2015) - Vilé, Gianvito; Albani, Davide; Nachtegaal, Maarten; Chen, Zupeng; Dontsova, Dariya; Antonietti, Markus; López, Núria; Pérez‐Ramírez, Javier
<x xml:space="preserve">Abstract</x> Most birds build nests to incubate their eggs and raise their young in a protective environment. In their Communication on page 11265 ff., J. Pérez‐Ramírez, N. López et al. apply a nesting concept to anchor isolated palladium atoms within the cavities of graphitic carbon nitride. This leads to a stable single‐site heterogeneous catalyst with outstanding performance in hydrogenation reactions (artwork concept: Amalia Gallardo, illustration: Marcel Reich).